*This preview shows
page 1. Sign up
to
view the full content.*

**Unformatted text preview: **3−0.1x 3. We ﬁrst note that we can rewrite the equation 9 · 3x = 72x as 32 · 3x = 72x to obtain 3x+2 = 72x .
Since it is not convenient to express both sides as a power of 3 (or 7 for that matter) we use
the natural log: ln 3x+2 = ln 72x . The power rule gives (x + 2) ln(3) = 2x ln(7). Even
though this equation appears very complicated, keep in mind that ln(3) and ln(7) are just
constants. The equation (x + 2) ln(3) = 2x ln(7) is actually a linear equation and as such we
gather all of the terms with x on one side, and the constants on the other. We then divide
both sides by the coeﬃcient of x, which we obtain by factoring.
(x + 2) ln(3)
x ln(3) + 2 ln(3)
2 ln(3)
2 ln(3)
x =
=
=
=
= 2x ln(7)
2x ln(7)
2x ln(7) − x ln(3)
x(2 ln(7) − ln(3)) Factor.
2 ln(3)
2 ln(7)−ln(3) Graphing f (x) = 9 · 3x and g (x) = 72x on the calculator, we see that these two graphs intersect
2 ln(3)
at x = 2 ln(7)−ln(3) ≈ 0.7866.
100
4. Our objective in solving 75 = 1+3e−2t is to ﬁrst isolate the expo...

View
Full
Document